Childhood Systemic Lupus Erythematosus: A Tertiary Care Centre Experience - Bajracharya, Luna; Thapa, Surya Bahadur (Journal of Nepal Paediatric Society, 2016)
Introduction: Systemic lupus erythematosus (SLE) is a chronic immunologic disorder with multisystem manifestations. Even more awareness is required to diagnose the disease at younger age. Objective of this study was to explore clinico-laboratory manifestations and management of SLE in children at Tribhuvan University Teaching Hospital (TUTH). Materials and Methods: The study was retrospective hospital based study conducted from 15th July, 2008 to 14th July, 2014. Medical charts of all children and adolescent (6- 16years of age) with SLE admitted at TUTH were reviewed for analysis of data. Results: The total number of patients was 33, with 28(84.8%) girls and 5 (15.2%) boys. The mean age of diagnosis was 12.12 (SD 1.89). Facial puffiness (27.3%) and arthralgia (24.2%) were the commonest presentations at disease onset. The most frequent clinical features during the entire course of illness were edema (78.9%), anemia (69.7%) and fever (66.7%). Twenty three (69.6%) patients underwent renal biopsy in which class IV was the commonest lupus nephritis. The commonly used drugs after prednisolone were intravenous cyclophosphamide, intravenouse methylprednisolone and mycophenolate mofetil. Total 17 (51.5%) patients went into remission. Two patients died due to active lupus and four due to sepsis. Conclusion: Lupus nephritis was the commonest feature at disease onset, at the time of diagnosis and throughout the disease course among Nepalese children with SLE. The most frequently used medications were prednisolone and iv cyclophosphamide. Infection and active lupus were the leading causes of complications and death. J Nepal Paediatr Soc 2015;35(2):111-116